Sustaining Infection Prevention and Control Post-Accreditation: A Systematic Review and Meta-Analysis of Global Longitudinal Outcomes - Adhika Rahman; Siswanto Pabidang (Community Medicine and Education Journal, 2026)
Hospital accreditation is globally recognized as a strategic framework for standardizing healthcare quality. However, the long-term efficacy of accreditation in sustaining Infection Prevention and Control (IPC) practices and reducing Healthcare-Associated Infections (HAIs) remains fiercely debated. Most existing literature relies on cross-sectional data, failing to capture the temporal stability of post-accreditation outcomes. A systematic review and meta-analysis were conducted following PRISMA guidelines. We analyzed longitudinal, interrupted time-series, and pre-and-post research articles evaluating IPC compliance and HAI incidence before, during, and after accreditation cycles. Data extraction focused on sample sizes, means, and standard deviations to calculate the Standardized Mean Difference (SMD) using a DerSimonian-Laird random-effects model. Heterogeneity was assessed via the I-squared statistic. Eight longitudinal studies encompassing varying international healthcare contexts were included. The pooled meta-analysis demonstrated a statistically significant, moderate improvement in IPC outcomes post-accreditation, with an overall SMD of 0.52 (95 percent Confidence Interval: 0.38 to 0.66, p < 0.001). Subgroup analyses revealed that structural IPC compliance measures showed higher effect sizes (SMD = 0.58) compared to direct clinical outcomes like HAI incidence density reductions (SMD = 0.42). Moderate heterogeneity was observed (I-squared = 54 percent). In conclusion, hospital accreditation acts as a significant catalyst for improving IPC metrics over time. The moderate effect size on direct clinical outcomes suggests that accreditation provides a structural foundation that must be coupled with continuous quality improvement and strong institutional leadership to prevent post-survey decay.